Abstract ID: 21 Simulation of synchrotron-based microbeam radiation therapy using Geant4. (October 2017) - Guatelli, Susanna; Cameron, Matthew; Dipuglia, Andrew; Davis, Jeremy; Cornelius, Iwan; Rozenfeld, Anatoly; Lerch, Michael
Abstract : Microbeam Radiation Therapy (MRT) is a preclinical radiotherapy modality characterised by the use of many micron-sized, spatially fractionated, high intensity radiation fields produced by a Multi-Slit Collimator and synchrotron light[1] . A typical MRT radiation field consists of multiple high dose 'peaks' separated by low dose 'valleys' (width 25–50 μm; pitch 100–400 μm) delivered with dose rates of up to 10 kGy/s. The minute field size and high dose rate of MRT requires good Quality Assurance in order to transition into the clinical field. Dose Verification and Treatment Planning Systems (TPS) are crucial aspects of quality assurance, allowing for independent prediction and verification of dose distributions delivered to patients. The most accurate form of TPS is Monte Carlo computer simulations. The Centre for Medical Radiation Physics (CMRP), University of Wollongong, has developed a Geant4-based synchrotron beamline model for dose verification at the Australian Synchrotron Imaging and Medical Beamline (IMBL). This model, denoted G4IMBL, uses a multi-stage procedure to generate synchrotron light, transport through the beamline model, and calculate dose deposition in a phantom. G4IMBL models the production of X-ray photons entirely using Geant4 by transporting electrons through the sinusoidal magnetic field of a wiggler. This allows for optimisation of multiple operation modes via tuning of wiggler magnetic field strength and electron steering angle. The simulation has been validated against experimental measurements and is used to characterise novel Quality Assurance silicon based detectors with sub-mm spatial resolution, developed at CMRP. The development, optimisation, and validation of this Geant4-based software tool for MRT Quality Assurance will be presented.